Religion and secularity : transformations and transfers of religious discourses in Europe and Asia - Eggert, Marion. (Dynamics in the History of Religions, 2013)
Religion and Secularity traces the history of the conceptual binary of religion and secularity in Europe and the repercussions it had in other regions and cultures of the Eurasian continent during the age of imperialism and beyond. Twelve authors from a wide range of disciplines, deal in their contributions with the trajectory, the concepts of "religion" and "secularity/secularization" took, as well as with the corresponding re-configurations of the religious field in a variety of cultures in Europe, the Near and Middle East, South Asia and East Asia. Taken together, these in-depth studies provide a broad comparative perspective on a penomenon that has been crucial for the development of globalized modernity and its regional interpretations.